Avaliação do perfil evolutivo da retocolite ulcerativa em ambulatório de referência brasileiro para doenças intestinais, no período de 20 anos - Ricardo Pereira Mendes (2016)
Ulcerative colitis (UC) is characterized by recurring episodes of inflammation limited to the mucosal layer of the colon. Although the disease can be potentially curative with proctocolectomy, medical therapies are the mainstay of treatment. The aim of the study was to evaluate the behavior of UC over 20 years from an InflammatoryBowel Disease Referral Center in Brazil. A longitudinal retrospective analysis of 101 patients with UC was conducted. The characteristics of patients and their diseases were described, and the cumulative probabilities of receiving medical therapies were assessed using the Kaplan-Meier method. Median age at diagnosis was 34 years, with a female preponderance. 14% of patients had proctitis, 42% leftsidedand 40% extensive colitis. Cumulative probabilities of receveing 5-aminosalicylic acid at 1 year and 10 years were 78% and 90%, respectively. Cumulative probabilities of receiveing immunosuppressants at 1 year and 10 years were 15% and 59%, respectively. There was, over the years, a trend of reduction in the need for corticosteroid therapy. In the year of diagnosis, 62.1% of patients used corticosteroids and, in the tenth year, this rate was 28.3%. It was concluded that some epidemiological data differ from the literature, as higher female prevalence and higher percentage of extensive colitis at the diagnosis. It was observed thatmost patients required immunosuppressants to achieve clinical remission. Patients older than 50 years at diagnosis had less need to initiate immunosuppressive therapy, and its use wasnt associated with the extent of the disease.